MESIODENTES AS A MECHANICAL OBSTACLE IN THE ERUPTION OF PERMANENT TEETH- CASE REPORT - Bochvarov, Aleksandar; Baldziev, Dejan; Temelkov, Oliver; Temelkova, Simona; Simjanovska, Ljuba; Arsovska, Mirjana Markovska (Journal of Morphological Sciences, 2022)
The aim of this paper is to emphasize the importance of the early detection of supernumerary teeth / mesiodentes that can cause mechanical obstruction in the eruption of permanent teeth and lead to irregularities in the dentition. We present a case of a ten-year-old child who was diagnosed with two mesiodentes and non- erupted permanent central incisors in the upper jaw. The absence of the central permanent incisors was clinically diagnosed and the presence of the mesiodentes was diagnosed with an X-ray. Mesiodentes were positioned below the permanent teeth and on the palatal side. The mechanical obstruction for normal eruption of the permanent incisors was removed when the mesiodentes were extracted under local anesthesia. The childâ€™s condition was excellent and after seven days the sutures were removed. After two and a half months, one of the central incisors erupted. Early detection of mesiodens is an important element for the normal eruption of permanent teeth and proper placement in the dental arch. Keywords : supernumerary teeth, mesiodens, upper jaw, suture.   https://doi.org/10.55302/JMS2251127b